Experience of Idursulfase Beta Administration in the Child with Mucopolysaccharidosis Type II: Clinical Case - Tatiana K. Kruchina; Konstantin V. Bruchikov; Gennady A. Novik (Вопросы современной педиатрии)
Background. Mucopolysaccharidosis type II (MPS II, Hunter syndrome) is a rare hereditary lysosomal storage disease associated with iduronate-2-sulfatase deficiency. Patients with MPS II require life-long enzyme replacement therapy (ERT) to replace the deficiency of endogenous enzyme. There are two medications — idursulfase and idursulfase beta — that are licensed and recommended for these patients in Russian Federation. However, it is well known that ERT can cause hypersensitivity reactions development.Clinical Case Description. The ERT (idursulfase in the dose of 0.5 mg/kg once per week) onset in the male patient with severe MPS II was at the age of 2.5 years. Hypersensitivity reactions (urticaria, fever) were noted incidentally, thus, the premedication with antihistamines and antipyretics was performed. The ERT side effects has aggravated at the age of 8 years despite the glucocorticosteroids admission and infusion rate reduction up to 8–16 ml/h. That is why we have changed the medication on idursulfase beta with major clinical response: we have achieved control on both disease itself and hypersensitivity reactions.Conclusion. The availability of two ERT medications for patients with MPS II expands treatment opportunities. In case of any allergic reactions due to idursulfase, the change on idursulfase beta reduces the risk of any ERT complications with sufficient control of MPS II course.